The Influence Of Online Customer Reviews, Online Customer Ratings And Free Shipping On Purchase Decisions Through The Shopee Marketplace (Case Study of 5th Semester Management Students) - Maryati, Sri; Kusuma, Merta (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2024)
The title of this research is The Effect of Online Customer Review, Online Customer Rating and Free Shipping on Purchasing Decisions through the Shopee Marketplace (Case Study of 5th Semester Management Students). The purpose of the study was to determine which factors are most dominant in influencing purchasing decisions. This study uses pourpuse sampling technique, namely population members have certain characteristics, namely those who use the shopee application directly as targets and research objects. This study uses quantitative methods on 65 respondents. The population used in this study were 5th Semester Management Students and the sampling in this study was random sampling. Based on the results of multiple linear regression, the regression equation Y = 4.236 + 0.774 (X_1) + 0.490 (X2) + 1.322 (X3) is obtained. And the coefficient of determination R. Square (R2) obtained a value of 0.791 or 79.1% on purchasing decisions in the shopee marketplace. While the remaining 0.209 or 20.9% is influenced by other variables that are not included in this research model. The research results and hypotheses show that Online Customer Review, Online Customer Rating, and Free Shipping have a positive and significant effect both partially and simultaneously on Purchasing Decisions.